Neuromarketing indicators of the perception of terroir stories in social media video content - Burdinskyi, Ivan (Актуальні питання економічних наук, 2025)
The article examines the concept of terroir as an element of marketing communications and its role in shaping brand authenticity. It is substantiated that the combination of terroir storytelling and video marketing on social media fosters an emotional connection between the brand and the consumer, thereby strengthening trust, loyalty, and a positive perception of products associated with a specific territory. The purpose of the study is to summarize scientific approaches to the analysis of terroir in marketing communications and to systematize neuromarketing indicators for assessing the perception of terroir video stories on social media. The methodological basis of the research is an interdisciplinary approach that combines the analysis of modern theories of storytelling, brand authenticity, and neuromarketing methods. Content analysis of scientific sources and the method of systematization were used to generalize approaches to measuring emotional engagement and audience reactions to video content. The article presents a description of key neuromarketing indicators for analyzing video materials with terroir-related narratives. The proposed formulas for calculating indicators enable quantitative measurement of consumers’ emotional and cognitive reactions and comparison of the effectiveness of different video strategies. The research results demonstrated that the effectiveness of video storytelling increases when authentic visual images, realistic emotions, and natural environmental elements are combined. Video content that reflects nature, traditions, people, and production processes activates positive emotional responses, enhances brand trust, and creates a sense of belonging to the place of product origin. The application of neuromarketing indicators in the study of such content ensures a scientifically grounded assessment of emotional engagement and viewers’ perception of terroir stories. Conclusions. The use of neuromarketing indicators enables more accurate evaluation of video storytelling effectiveness, optimization of brand communication strategies, and stronger positioning in the digital environment. The obtained results can be used for further research in the fields of neuromarketing, place branding, and emotional content marketing.